1998
DOI: 10.1038/sj.onc.1201811
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between the RING+B1-B2 and coiled-coil domains of PML is necessary for its effects on cell survival

Abstract: PML/RARa is the abnormal protein product of the Acute Promyelocytic Leukemia-speci®c 15;17 translocation. Both the PML and RARa components are required for the PML/RARa biological activities, namely its capacity to block di erentiation and to increase survival of haematopoietic precursors. The physiological role of PML and its contribution to the function of the fusion protein are unknown. PML localizes to the cytoplasm and within speci®c nuclear bodies (NBs). In vitro, overexpression of PML correlates with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 28 publications
(43 reference statements)
5
47
0
Order By: Relevance
“…The apoptotic activity of PML appears to be mediated through its RING domain (24). In addition, deletion of the coiled-coil motif in PML yields a diffuse nuclear localization pattern and results in no growth suppression (50). Although MAIR is a cytoplasmic protein rather than a nuclear protein, corresponding regions of MAIR appear to be required for the apoptosis-inducing activity.…”
Section: Tissue Distribution and M-csf-induced Expression Ofmentioning
confidence: 99%
“…The apoptotic activity of PML appears to be mediated through its RING domain (24). In addition, deletion of the coiled-coil motif in PML yields a diffuse nuclear localization pattern and results in no growth suppression (50). Although MAIR is a cytoplasmic protein rather than a nuclear protein, corresponding regions of MAIR appear to be required for the apoptosis-inducing activity.…”
Section: Tissue Distribution and M-csf-induced Expression Ofmentioning
confidence: 99%
“…Another study concluded that nuclear localization of PML is required for its growth-suppressive function. In this study, a PML cytoplasmic isoform did not yield an appreciable effect on cell growth inhibition when compared with a PML nuclear isoform (Fagioli et al, 1998). Owing to lack of any known functions for the cytoplasmic isoforms by these studies, research on PML in this decade has focused exclusively on the nuclear isoforms.…”
Section: Role Of Cytoplasmic Promyelocytic Leukemia Pml (Cpml) In Tgfmentioning
confidence: 99%
“…PML was originally identified as the fusion partner with the retinoic acid receptor RARalpha in leukemic blasts from patients suffering from acute promyelocytic leukemia (APL), leading to disrupted PML-NBs (Melnick and Licht, 1999). Accumulating evidence indicates that PML-NBs play regulatory roles in cellular processes such as cell growth (Fagioli et al, 1998;Cohen et al, 2001), chromatin remodeling (Amin et al, 2001), cellular differentiation (Drouin et al, 2001), protein degradation (Lallemand-Breitenbach et al, 2001), transcriptional regulation (Li et al, 2000;Zhong et al, 2000), antiviral response (Everett, 2001;Regad and Chelbi-Alix, 2001), cellular senescence (Ferbeyre et al, 2000;Pearson et al, 2000;Bischof et al, 2002;Langley et al, 2002), tumor suppression (reviewed by Salomoni and Pandolfi (2002)), DNA repair (Bischof et al, 2001;Carbone et al, 2002) and apoptosis (Wang et al, 1998;Fogal et al, 2000;Guo et al, 2000;D'Orazi et al, 2002;Hofmann et al, 2002).…”
Section: Introductionmentioning
confidence: 99%